Bmi deficiency causes oxidative stress and intervertebral disc degeneration which can be alleviated by antioxidant treatment. Issue 16 (24th June 2020) - Zhang, Qunhu; Li, Jie; Li, You; Che, Hui; Chen, Ying; Dong, Jianghui; Xian, Cory J.; Miao, Dengshun; Wang, Liping; Ren, Yongxin
Abstract: The transcriptional repressor Bmi‐1 is involved in cell‐cycle regulation and cell senescence, the deficiency of which has been shown to cause oxidative stress. This study investigated whether Bmi‐1 deficiency plays a role in promoting disc degeneration and the effect of treatment with antioxidant N‐acetylcysteine (NAC) on intervertebral disc degeneration. Bmi‐1 −/− mice were treated with the antioxidant NAC, supplied in drinking water (Bmi‐1 −/− +NAC). For in vitro experiments, mouse intervertebral discs were cultured under low oxygen tension and serum‐limiting conditions in the presence of tumour necrosis factor α and interleukin 1β in order to mimic degenerative insult. Disc metabolism parameters in these in vitro and in vivo studies were evaluated by histopathological, immunohistochemical and molecular methods. Bmi‐1 −/− mice showed lower collagen Ⅱ and aggrecan levels and higher collagen Ⅹ levels than wild‐type and Bmi‐1 −/− +NAC mice. Bmi‐1 −/− mice showed significantly lower superoxide dismutase (SOD)‐1, SOD‐2, glutathione peroxidase (GPX)‐1 and GPX‐3 levels than their wild‐type littermates and Bmi‐1 −/− + NAC mice. Relative to Bmi‐1 −/− mice, the control and Bmi‐1 −/− +NAC mice showed significantly lower p16, p21, and p53 levels. These results demonstrate that Bmi‐1 plays an important role in attenuating intervertebral disc degeneration in mice by inhibiting oxidative stress and cell apoptosis.